Pengembangan Media Pembelajaran Box Nusantara untuk Membentuk Kemampuan Memahami Konsep Tematik pada Siswa Sekolah Dasar - Sintayana Muhardini; Nanang Rahman; Mahsup Mahsup; Raden Sudarwo; Khaerul Anam; Sukron Fujiaturrahman (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of this research is to address the problems relating to the lack of interesting and effective x thematic learning media in class so as to improve the effectiveness of learning. The development procedure refers to the Borg & Galls procedure with the development research procedure which consists of two main objectives, namely developing the product and validating the resulting product. The population of this study was SDN 1 and SDN 2 Sesela and the research samples used were SDN 1 Sesela as many as 12 students and at SDN 2 Sesela as many as 27 students. The research instruments used were questionnaires to validate and evaluate the quality of the developed products. Data analysis teschniques used qualitative descriptive and descriptive statistic analysis. The results of the research were as follows: (1) The results of expert validation and teacher assessment of media products that have been developed eligible to be used, (2) Limited trial results are known that the product development is worth use and (3) field trial results are known that the product of development that has been worthy of use affects the ability to understand the students ' thematic concept.